2021
DOI: 10.1021/acsnano.1c04056
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Symmetry Breaking at the Single-Particle Level via the Growth of Tetrahedron-Shaped Nanocrystals from Higher-Symmetry Precursors

Abstract: The vast majority of single crystalline metal nanoparticles adopt shapes in the O h point group as a consequence of the symmetry of the underlying face-centered cubic (FCC) crystal lattice. Tetrahedra are a notable exception to this rule, and although they have been observed in several syntheses, their growth mechanism, and the symmetry-reduction process that necessarily characterizes it, is poorly understood. Here, a symmetry breaking mechanism is revealed by in situ liquid flow cell transmission electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…(B) In situ TEM images and the corresponding geometrical models showing the transition from a rhombic dodecahedron to a tetrahedron (scale bars: 25 nm). Adapted with permission from ref . Copyright 2021 American Chemical Society.…”
Section: Summary and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…(B) In situ TEM images and the corresponding geometrical models showing the transition from a rhombic dodecahedron to a tetrahedron (scale bars: 25 nm). Adapted with permission from ref . Copyright 2021 American Chemical Society.…”
Section: Summary and Outlookmentioning
confidence: 99%
“…In a recent paper, a versatile method was reported for effectively screening more than one reaction parameters to capture and scrutinize specific symmetry breaking behaviors (Figure 45). 423 By flushing the metal precursor (HAuCl 4 ) solution into a liquid cell to create continuous and opposing concentration gradients of HAuCl 4 and ligands (cetylpyridinium chloride and CTAB), a variety of reaction conditions for the growth from Au rhombic dodecahedral seeds were probed in one experiment. It was found that at relatively high and low concentrations for the ligands and precursor, respectively, conformal growth of the seeds gave rise to pseudospherical nanocrystals (i.e., the thermodynamic product), whereas the opposite conditions resulted in a dendritic morphology (i.e., the kinetic product).…”
Section: Advanced Characterization Techniquesmentioning
confidence: 99%
“…2b), consistent with those reported in the literature. 25 The reason for obtaining tiny Au NPs is that [B 12 H 12 ] 2− is immobilized on the surface of HNTs, and correspondingly formed Au NPs cannot agglomerate in large quantities compared with Na 2 B 12 H 12 @Au (Fig. S2 †).…”
Section: Resultsmentioning
confidence: 99%
“…Salassi et al highlight how different shapes and sizes of AuNPs lead to their different kinds of wrapping with organic ligands. Not surprisingly, other recent works have shown evident effects of the NP surface topology on specific polymer adsorption. …”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, other recent works have shown evident effects of the NP surface topology on specific polymer adsorption. 26 28 …”
Section: Introductionmentioning
confidence: 99%